STUDY OF BEACHROCKS IN EAST ATTICA - Karkani, A.; Evelpidou, N.; Maroukian, H.; Kawasaki, S. (Bulletin of the Geological Society of Greece, 2016)
Sea level indicators, such as tidal notches and beachrocks, may provide valuable information for the relative sea level changes of an area. Beachrocks in particular have received various arguments concerning their use as reliable sea level indicators and their formation environment. This work focuses on the coasts of East Attica in order to trace the palaeoshorelines of the Upper Holocene through the study of beachrocks. The coastal zone was surveyed in detail by snorkelling and diving, in order to locate, map and sample beachrocks. The samples were studied under a SEM, which showed that the beachrocks are mainly composed of quartz grains, a few calcites and feldspars, while the carbonate cement is characterized with the presence of MgO at percentages between 5 and 7.8%. Based on correlations with published drillings in the study area, the studied beachrocks should not be older than 2000 years BP.